Optimal design for the free-stream water wheel: A two-dimensional study. (1st January 2021) - Cleynen, Olivier; Engel, Sebastian; Hoerner, Stefan; Thévenin, Dominique
Abstract: Free-stream water wheels running on floating river installations may contribute to hydropower production as part of a decentralized network meeting the highest ecological standards. While such devices are certainly not novel, their dynamics are complex and a need exists for an optimization of their power-producing characteristics. In this work, a parametrized two-dimensional computational fluid dynamics simulation is coupled to a genetic optimizer seeking to maximize the generated shaft power within a large domain of design parameters. Two objectives are pursued simultaneously: maximize the hydraulic efficiency, and maximize the power density of the device. After nearly 2000 individuals are evaluated, a Pareto front is identified; a family of designs is created to cover the trade-off between the two objectives. The results indicate that compared to operators constrained by the flow-exposed area, operators constrained by the rotor size would trade a 40% reduction in hydraulic performance in order to gain a 50% increase in power per unit rotor area. This optimization of the free-stream water wheel, the first in published literature to our knowledge, allows for the quantification of this trade-off and the publication of broadly-applicable design guidelines for the corresponding optimal blade geometry, number of blades, radius, and depth. Highlights: The free-stream water wheel, used on floats in rivers, is an underused hydropower device with very low ecological impact. 2000 two-dimensional simulations are carried out to optimize its design with a genetic algorithm. Design guidelines are created, according to whether operators want to maximize hydraulic performance or power density.